Neurophysiology in Clinical Practice - Rana, Abdul Qayyum; Ghouse, Ali T.; Govindarajan, Raghav; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This handbook provides a concise up to date review in interpreting electroencephalography and electromyography using simple illustrations. The book has been divided into two sections. Section 1 describes electroencephalography and Section 2 discusses electromyography and nerve conduction studies. Each chapter has been carefully drafted to provide the most up to date accurate information in an easy to understand format interspersed with diagrams and tables where needed. This book is aimed at trainees doing their neurophysiology rotation, general neurologists, general practitioners, advanced practice providers and neurophysiology technicians.
Section 1: Electroencephalography -- Electroencephalography -- Section 2: Electromyography and Nerve Conduction Studies -- Clinical Evaluation -- Instrumentation -- Nerve Conduction Studies -- Sensory Neuropathies -- Nerve Trauma -- Peripheral polyneuropathy -- Radiculopathy -- Plexopathy -- Median Neuropathy -- Ulnar Neuropathy -- Radial Neuropathy -- Lower Extremity Neuropathy -- Motor Neuron Disease / Amyotrophic Lateral Sclerosis -- Autonomic Neuropathy -- Neuromuscular Transmission Disorders -- Myopathy -- Cranial Nerves -- Somatosensory Evoked Potentials.
Keywords: Medicine; Neurology; Medicine & Public Health; Neurology